Enterocutaneous fistula in incisional hernia: unsual complication - Gentile, João Kleber de; Chryssocheri Mauá, Ana Carolina; Lazarini, Leonardo; Medeiros Trajdecki, Melanie; Pinto Ambar, Gabriela Póvoas (Brazilian Journal of Case Reports, 2022)
Enterocutaneous fistula is defined as an abnormal communication between the intestinal lumen and the skin usually associated with abdominal surgeries, trauma, Crohn's disease, hernia mesh erosions and diverticulitis. We report a case of 46-year-old male, obese, referred to general surgery for enterocutaneous fistula in hernia sac. He had undergone exploratory laparotomy for gunshot wound to the abdomen 6 years ago where he underwent subtotal colectomy, splenectomy and terminal ileostomy with amputation of the rectal stump. In the current case report, obesity and surgical technique at laparotomy closure (a history of major exploratory laparotomy for gunshot wound) were the risk factors associated with the appearance of the fistula. Moreover, there was presence of midline incisional hernia with small bowel loops inside the hernia sac, which according to the European Commission Hernia Society should be avoided because it facilitates the formation of fistulas.